Japan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2000)
A sustained decline in fertility rates underlies a rapid aging and decline of Japan's population. This will have profound social and economic implications. The paper illustrates the difficult situation facing Japanese fiscal policy in the years ahead. The findings of this paper indicate that there may be a role for foreign exchange interventions in providing stimulus at the current conjuncture. Deposit insurance reform is a central element in the government strategy to strengthen the Japanese banking system. The unemployment-deflation puzzle in Japan has been explained.